Dual role of complement in neuronal repair - Lukomska, Agnieszka; Ciesielski, Peter; Ratajczak, Mariusz Z.; Kucia, Magdalena (Frontiers in Immunology, 2025)
The complement system, long regarded as an arm of innate immunity, is now recognized as an important modulator of nervous system pathophysiology. Following acute injury or in chronic neurodegenerative diseases, promoting neuronal survival and axon regeneration remains a formidable clinical challenge. This review synthesizes the extensive, paradoxical evidence of complement’s dual role in neurodegeneration and repair. We examine how complement activation is both detrimental—driving neuroinflammation, apoptosis, and pathological autophagy via receptors like C5aR1 and its interaction with the NLRP3 inflammasome—and beneficial, promoting C5a-mediated phagocyte recruitment for debris clearance and C3-dependent synaptic stripping for circuit remodeling. This review’s unique contribution is its integration of these classic extracellular pathways with the recently discovered intracellular complement system, or ‘complosome.’ We explore how the complosome offers a novel mechanistic framework linking complement to fundamental cellular processes, including metabolism and survival, particularly through its intricate connection with the master regenerative mTOR pathway. This highlights complement not as a simple inflammatory switch, but as a sophisticated signaling network. Understanding this duality is essential for developing therapies that selectively suppress complement-driven damage while enhancing its regenerative functions.